Correlation Between Self-acceptance and Quality of Life in People with Hypertension - Muhammad Fajar Afnizar; Fahrun Nur Rosyid (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Low level of self-acceptance and quality of life often be one of the main problem faced by people with hypertension. Changes in many aspects of everyday life lead to the decrease of many physical and mental abilities of patients. Thiese abilities including their ability to cope mentally to their condition which is self-acceptance, and also their ability to adapt their physical conditiona to the new life style after hypertension which is quality of life. This research aims to determine the relationship between the level of self-acceptance and the hypertension sufferer's quality of life in The Kartasura Health Center working area. the research used a cross-sectional correlational analitic design which was carried out at The Kartasura Health Center in the period March - July 2024. The population of this research were 515 hypertension patients. The sample consisted of 215 participants taken through accidental sampling by taking random patients who checked themselves to Kartasura Health Center the days when the research occurred. Data collecting of this research using two kind of questionnaires. Self-acceptance measured through Unconditional Self-Acceptance Questionnaire (USAQ). Hypertension sufferer's quality of life measured through WHOQOL-BREF Questionnaire. The results of this research were obtained through univariate and bivariate test. Univariate analysis showed that the majority of people with hypertension had a moderate level of self-acceptance (75.3%) and a moderate level of quality of life (66%). Bivariate analysis correlation test with Spearman Rank showed that there is a significant relationship between the level of self-acceptance and the quality of life of people with hypertension (p-value = 0.000). Policy such as including not only physical but also mental-emotional check up and treatments such as emotional support therapy, behavioral therapy, mental counseling, and in team activities into posyandu and posbindu could be a good step to solve these problems. Keyword: Hypertension, Quality of Life, Self-acceptance